The relationship between perceived stigma and perceived stress in cognitive decline: a survey of persons with mild cognitive impairment and their caregivers - Warren, Alison (Frontiers in Psychology, 2023)
While Alzheimer's disease and other causes of dementia have rapidly become a global health crisis with growing incidence that is unabated, the incidence of Mild Cognitive Impairment (MCI) far exceeds that of Alzheimer's disease. Persons with MCI demonstrate some level of cognitive impairment, but daily functions remain intact and there is no certainty that they will develop dementia. Yet, the possibility conjures a considerable amount of fear and anxiety, further fueled by a vast array of misconceptions and stigma. The pervasive nature of this stigma permeates society and culture at many levels. Persons with MCI who are at higher risk for development of dementia may be especially vulnerable to fear and stigma associated with the diagnosis. Based on this premise, the primary aim of this study was to examine the relationship between perceived stigma and perceived stress in persons with MCI and their care partners, including the relationship between income and the study variables. The secondary aim was to examine the effect of a combined cognitive rehabilitation and wellness program on these perceptions. Thirty participants were recruited from Mayo Clinic's Health Action to Benefit Independence and Thinking (HABIT) program. MCI (n=15) and care partner (n=15) participants completed the Stigma Impact Scale (SIS) and the Perceived Stress Scale (PSS) before and after the HABIT program. Average SIS and PSS scores decreased in the MCI, care partner, and combined groups, both pre-and post-HABIT. Linear regression was used to assess the relationship between perceived stigma and stress, controlling for income. A significant relationship was found between perceived stigma and perceived stress both pre and post-HABIT. The results suggest a relationship exists between perceived stigma and perceived stress in persons with MCI and their care partners, and an educational program such as HABIT may strengthen this relationship by informing participants of potential challenges that occur in cognitive decline. Understanding these relationships may provide an opportunity to provide tools for this vulnerable population.